2013
DOI: 10.1002/stem.1471
|View full text |Cite
|
Sign up to set email alerts
|

Thrombospondin-2 secreted by human umbilical cord blood-derived mesenchymal stem cells promotes chondrogenic differentiation

Abstract: Increasing evidence indicates that the secretome of mesenchymal stem cells (MSCs) has therapeutic potential for the treatment of various diseases, including cartilage disorders. However, the paracrine mechanisms underlying cartilage repair by MSCs are poorly understood. Here, we show that human umbilical cord blood-derived MSCs (hUCB-MSCs) promoted differentiation of chondroprogenitor cells by paracrine action. This paracrine effect of hUCB-MSCs on chondroprogenitor cells was increased by treatment with synovi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
98
0
1

Year Published

2014
2014
2020
2020

Publication Types

Select...
8
1
1

Relationship

1
9

Authors

Journals

citations
Cited by 103 publications
(102 citation statements)
references
References 60 publications
1
98
0
1
Order By: Relevance
“…Mesenchymal stem cells derived from human umbilical cord blood (hUCB-MSCs) are characterized by self-renewal [1], a potential for differentiation into multiple cell lineages [2], low immunogenicity [3], and paracrine functions [4][5][6], suggesting that they may be beneficial in allogeneic MSC-based therapy. However, enabling MSC-based therapy requires expanding MSCs in large-scale production via long-term in vitro cultivation.…”
Section: Introductionmentioning
confidence: 99%
“…Mesenchymal stem cells derived from human umbilical cord blood (hUCB-MSCs) are characterized by self-renewal [1], a potential for differentiation into multiple cell lineages [2], low immunogenicity [3], and paracrine functions [4][5][6], suggesting that they may be beneficial in allogeneic MSC-based therapy. However, enabling MSC-based therapy requires expanding MSCs in large-scale production via long-term in vitro cultivation.…”
Section: Introductionmentioning
confidence: 99%
“…Thus, our study suggests that PML may regulate Schwannian differentiation within neuroblastoma tumors via angiogenesis inhibition or that TSP2 itself may have direct prodifferentiation properties in vivo. In keeping with this, TSP2 has been shown to induce synaptogenesis in the central nervous system (49) and chondrogenic differentiation in the bone (50).…”
Section: Discussionmentioning
confidence: 66%
“…It was previously demonstrated that CM of hUCB-MSCs contain active levels of a number of disease modifying growth factors and cytokines. 21,22 CM of hUCB-MSCs contain sizable levels of angiopoietin, hepatocyte growth factor, interleukin-4, insulin-like growth factor, placental growth factor, vascular endothelial cell growth factor, angiogenin, stem cell factor, and tyrosine hydroxylase. 5,[23][24][25] Our previous studies demonstrated the neuroprotective effects of conditioned media from hADSC and hNSC in rat models of stroke and Huntington's disease.…”
Section: Discussionmentioning
confidence: 99%